Economics of Tubewell Irrigation - Dhawan, B.D. (Journal of Soil and Water Conservation, 2022)
Optimal size of a public tubewell is around 2.5 cosec capacity. Beyond this size, the scale economies are marginal, and not worth exploiting because of inter alia adverse external effects on other users of groundwater. Groundwater extraction capacity of a tubewell being much more than that of a traditional well, tubewell irrigation generates a tendency of overdraft on groundwater acquifer, giving rise to a downward pressure on water table. A continual decline in water table has serious implications. Also, proximity in location proves detrimental in the short-run, especially for a well owner having a lower capacity waterlift. In this context it is advocated that excessive reliance on tubewell irrigation be avoided. Instead, the reliance be placed on conjunctive exploitation of ground and surface waters. Exploitation of groundwater directly under state auspices is recommen- ded if (a) the state is confident of managing the public tubewell system efficiently, and (b) there is preponderance of small and fragmented holdings. Being a perennial source of irrigatioa tubewell encourages crop activity throughout the year. Its dependability during drought permits crop intensification of a high level.